Вплив мегатрендів: методологічні засади оцінки стійкості ритейлу в контексті системи життєзабезпечення - Гапоненко, Ольга Євгенівна; Кизлюк, Олександр Анатолійович (ТОВ "ДКС Центр", 2025)
У статті розглядається проблема впливу сучасних мегатрендів на розвиток ритейлу як ключового елементу національної системи життєзабезпечення. Актуальність теми зумовлена необхідністю адаптації бізнес-моделей ритейлу до глобальних викликів, зокрема цифровізації, урбанізації, демографічних змін, екологічного тиску, зростання вимог до якості продукції та трансформації споживчої поведінки. На основі аналізу сучасних наукових праць та доповідей міжнародних дослідницьких центрів встановлено, що мегатренди мають подвійний характер – вони створюють як ризики, так і нові можливості для забезпечення стійкості ритейлу. Метою дослідження є розробка підходу до оцінки стійкості ритейлу в системі життєзабезпечення, яка поєднує системний підхід, концепцію резильєнтності та інструменти ризик-менеджменту. У роботі визначено критерії адаптаційної здатності ритейлу до окремих мегатрендів та запропоновано в подальшому використати інтегральний індекс його впливу на стабільність системи життєзабезпечення. Результати мають як теоретичне значення для розробки економіки стійкості, так і практичне – для формування стратегій розвитку бізнесу в умовах глобальних трансформацій. The article addresses the problem of assessing the impact of global megatrends on retail development as a strategic component of the national lifesupport system. Megatrends are defined as long-term structural shifts that shape political, economic, technological and social transformations on a global scale. Their significance lies in the fact that they simultaneously generate systemic risks and open new opportunities that determine the resilience of the retail sector. The study is conceptually based on the system approach, risk management theory and the concept of resilience, understood as the ability not only to withstand shocks but also to adapt and recover through innovation. Existing research emphasizes megatrends such as technological revolution and digital culture, rapid urbanization, demographic shifts, sustainable development challenges, health imperatives, and globalization of business. Although many works have recognized their influence, the problem of measuring the adaptive capacity of national retail systems relative to megatrends remains insufficiently resolved. The research goal is to elaborate a model for evaluating retail resilience through a system of specialized indicators grouped by megatrend categories. Indicators include accessibility of goods, safety and reliability of supply, social orientation, adaptability of assortment, and efficiency of logistics under disruptive conditions. On this basis, the article proposes an integral index measuring the overall impact of retail on the stability of the life-support system of the population. The proposed approach highlights how adaptation strategies in retail, such as digital platforms, localized supply chains, support for local producers and sustainable product lines, may enhance resilience in times of crisis. The results are theoretically relevant for the development of resilience economics and practically useful for business strategies, public policy design and sustainable urban planning. The proposed methodology can be applied for monitoring risks, forecasting vulnerabilities and optimizing governance mechanisms of retail under conditions of accelerated global transformations.
Megatrends' impact: a methodological basis for assessing retail resilience in a life-support system context
Keywords: ритейл; система життєзабезпечення; мегатренди; retail; life support system; megatrends